Phytotechnology: potential of floaters as phytoindicator for nitrification and europhication in unhealthy freshwater bodies - Wan Muhamad, Wan Naimatul Asiah; Othman, Rashidi; Shaharuddin, Ruhul Izzati; Mohd Latiff, Nur Hanie (2012)
The aim of this research is to verify the potential of different floating macrophytes as a good phytoindicator for excess nutrients or bioindicator for nitrification and eutrophication in fresh water bodies. Domination of floaters in water bodies were investigated from 3 different states (Selangor, Pahang and Kelantan) in Malaysia. At each state, 15 water samples were collected and analysed for phosphate, ammonium, nitrite and nitrate. Species are varied at each site, namely Lemna minor, Eichhornia crassipes, @eptunia oleracea, Pistia stratiotes, Spirodela polyrhiza and Salvinia molesta. L.minor, E.crassipes and S.polyrhiza were observed as a great phytoindicator for excess nutrient of phosphate and ammonium. Water quality where both species were in abundance was classified in class III and considered polluted according to Interim @ational Water Quality Standards for Malaysia (I@WQS). This finding revealed that all water bodies were detected with the presence of excess nutrients but the levels of concentration are varied. All species were found as potential and effective phytoindicators for nitrification and eutrophication in fresh water bodies.